2018
DOI: 10.1002/bit.26781
|View full text |Cite
|
Sign up to set email alerts
|

A novel cytochrome P450 mono‐oxygenase from Streptomyces platensis resembles activities of human drug metabolizing P450s

Abstract: Cytochrome P450 mono-oxygenases (P450) are versatile enzymes which play essential roles in C-source assimilation, secondary metabolism, and in degradations of endo- and exogenous xenobiotics. In humans, several P450 isoforms constitute the largest part of phase I metabolizing enzymes and catalyze oxidation reactions which convert lipophilic xenobiotics, including drugs, to more water soluble species. Recombinant human P450s and microorganisms are applied in the pharmaceutical industry for the synthesis of drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 45 publications
0
29
0
Order By: Relevance
“…M8 with an m/z ratio of 735.3 is possibly corresponding to an oxidation of metabolite M5 to a ketone. This metabolite was described before in a biotransformation of ritonavir with a P450 of the strain Streptomyces platensis . Furthermore, products with the m/z ratio of 606.3 and 622.3 could be identified which were described as degradation products of ritonavir before and were also present in the sample directly taken after substrate addition .…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…M8 with an m/z ratio of 735.3 is possibly corresponding to an oxidation of metabolite M5 to a ketone. This metabolite was described before in a biotransformation of ritonavir with a P450 of the strain Streptomyces platensis . Furthermore, products with the m/z ratio of 606.3 and 622.3 could be identified which were described as degradation products of ritonavir before and were also present in the sample directly taken after substrate addition .…”
Section: Resultsmentioning
confidence: 93%
“…The screening resulted in nine strains showing good bioconversion rates of cyclosporine into the two human hydroxylated (AM1 and AM9) and N ‐demethylated (AM4) derivatives . In a recent study a novel P450 from the actinomycete Streptomyces platensis was identified showing high activity for the conversion of several pharmaceutical compounds while producing equivalent metabolites to the human metabolizing P450s 3A4, 2C8, 2C19, and 2D6 …”
Section: Introductionmentioning
confidence: 99%
“…According to the online P450 database CYPED 31 genes belong to the CYP105 and the CYP107 families. Fourteen of those genes (13 of S. platensis and 1 of P. autotrophica ) have been investigated in previous studies . One cyp gene in P. autotrophica has a length of only 378 bp and was not considered further.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, our group described nine metabolites of ritonavir biotransformed by the parent organism of both P450s Streptomyces platensis DSM 40041. Metabolites were analyzed by LC/MS and LC/MS‐MS analysis . The observed mass differences and retention times for 1 b – d correspond to the N‐dealkylated and N‐demethylated metabolites described there (Table S7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation